Pemberdayaan Kader dan Lansia Melalui Edukasi Pemanfaatan Bumbu Dapur Sehat di LKS Payung Besurek Kota Bengkulu - Marini Marini; Hesti Setiorini; Lussyefrida Yanti; Andry Sartika (Jurnal Pengabdian Kepada Masyarakat, 2026)
Elderly people are a vulnerable group experiencing declining body functions and an increased risk of degenerative diseases, requiring promotive and preventive efforts to maintain their health. One alternative is the utilization of kitchen spices as herbal drinks because they contain various bioactive compounds that are beneficial for health. However, knowledge among the elderly regarding the benefits and processing methods of herbal ingredients is still limited. This community service activity aimed to improve the knowledge and skills of elderly participants in utilizing kitchen spices as herbal drinks at LKS Payung Besurek Bengkulu City. The method used a participatory approach through educational sessions, interactive discussions, and direct practice in preparing herbal drinks. The results showed high enthusiasm from participants during the activities. Around 85% of participants experienced increased understanding of the health benefits of kitchen spices. Participants were also able to independently prepare herbal drinks using easily available local ingredients. In addition, the activity generated positive social impacts, including improved interaction, increased awareness of healthy lifestyles, and greater independence in maintaining health through natural ingredients. Therefore, this education program is an effective community-based health empowerment strategy for the elderly.